Analysis of the calligraphy design on selected Quranic phrases in the Blue Mosque Malaysia / Ahmed Abdulkadhim Crimsh - Ahmed Abdulkadhim, Crimsh (2017)
The Islamic world has developed many different types of arts since the advent of Islam. Calligraphy is one of the most prominent arts since that time, and it is considered to be parts and parcel of the Quran. Therefore, the Islamic Calligraphy is used to decorate mosques as well as other sacred places such as palaces, shrines, schools and other Islamic buildings. Calligraphy and other artistic elements used for decoration in mosques are meant for the appreciation, glorification and praising of sacredness of the mosques. Wonderful examples of Islamic calligraphy can be found in many mosques in Malaysia. However, in those mosques, calligraphy and other ornaments need to be documented to shed light on the styles implemented in the decoration process of their interior and exterior. Therefore, this research aims to study and analyze the aesthetic value of the Islamic calligraphy in a selected mosque known as the Blue Mosque (Sultan Salahuddin Abdul Aziz mosque) in Malaysia. The Blue Mosque has been selected in the present research due to the uniqueness in its decorations and architecture. Furthermore, it was chosen for the decorations of common Quranic verses written by different styles of Islamic calligraphy in the structure of the mosque. This study aims to show the necessity of studying the Islamic calligraphy used in the Blue Mosque and demonstrate the importance of using this calligraphy in the mosque. The study will also help to provide a new source of information that can be used by tour guides and the people who would like to understand and study the Islamic calligraphy applied on the Blue Mosque.